2022
DOI: 10.1002/mp.15682
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Respiratory impacts on static and respiratory gated 99mTc‐MAA SPECT/CT for liver radioembolization: A simulation study

Abstract: Purpose We aimed to evaluate respiratory impacts on static and respiratory gated (RG) 99mTc‐MAA SPECT in terms of respiratory motion (RM) blur, attenuation correction (AC), and volume‐of‐interest (VOI) segmentation on lung shunt faction (LSF) and tumor‐to‐normal liver ratio (TNR) estimation for liver radioembolization therapy planning. Methods The XCAT phantom was used to simulate a population of 300 phantoms, modeling various anatomical variations, tumor characteristics, RM amplitudes, LSFs, and TNRs. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Moreover, the ranges of motion used in the simulations are higher than those estimated for our patients: between 1 and 2 cm versus 0.9 cm in the cranio-caudal direction and between 0.6 and 1.2 cm versus 0.4 cm in the antero-posterior direction that could also explain differences in conclusions. There was no significant difference in the TN ratio between the two reconstructions in contrast to other authors who found an underestimation of the TN ratio in the absence of respiratory motion correction [ 23 , 24 ]. In the article by Bastiaannet et al [ 23 ], the lesions have a volume of less than 35 mL, in contrast to those of our patients (between 1.7 and 1828 mL).…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Moreover, the ranges of motion used in the simulations are higher than those estimated for our patients: between 1 and 2 cm versus 0.9 cm in the cranio-caudal direction and between 0.6 and 1.2 cm versus 0.4 cm in the antero-posterior direction that could also explain differences in conclusions. There was no significant difference in the TN ratio between the two reconstructions in contrast to other authors who found an underestimation of the TN ratio in the absence of respiratory motion correction [ 23 , 24 ]. In the article by Bastiaannet et al [ 23 ], the lesions have a volume of less than 35 mL, in contrast to those of our patients (between 1.7 and 1828 mL).…”
Section: Discussioncontrasting
confidence: 93%
“…Few studies have been published on the subject. In [ 23 , 24 ], the authors evaluated dosimetric impacts of motion by performing simulations from digital XCAT phantoms with different sets of parameters (body type, lung shunt fraction (LSF), tumor volume and localization). Likewise, Santoro et al [ 25 ] tested a novel method to compensate for motion on a modified CIRS dynamic phantom and applied it on the data of twelve selected patients (HCC, single lesion).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations